Does semen quality change after local treatment of seminal vesiculitis in stallions? - Sancler-Silva, Y. F.R.; Monteiro, G. A.; Ramires-Neto, C. [UNESP]; Freitas-Dell'aqua, C. P. [UNESP]; Crespilho, A. M.; Franco, M. M.J. [UNESP]; Silva-Junior, E. R. [UNESP]; Cavalero, T. M.S. [UNESP]; Scheeren, V. F.C. [UNESP]; Papa, F. O. [UNESP] (Elsevier, 2020)
Inflammation of the seminal vesicle interferes with fertility and is a persistent problem that is difficult to treat. The aim of this study was to evaluate the semen quality of 5 stallions with seminal vesiculitis before and after local treatment. All stallions were endoscopically treated for seminal vesiculitis during 10 consecutive days. The glandular lumen was accessed and flushed with a Ringer Lactate solution prior to antibiotic infusion. The antibiotic was selected based on the antibiogram from bacterial culture of samples previously collected from the seminal vesicles. The kinetic parameters (total motility – TM; progressive motility – PM; and rapid sperm - RAP), plasma membrane integrity (PMI), percentage of leukocyte (LEUK) and colony forming units (CFU) of fresh semen samples were evaluated. Additionally, nitric oxide (NO) content in seminal plasma was measured. All parameters were assessed before (T0), one week after treatment (T1) and one month after therapy (T2). The sperm kinetics and plasma membrane integrity showed an improvement in T1 that didn't last until T2. Percentage of leukocytes and CFU decreased on fresh semen and NO decreased on seminal plasma at T1 but were similar between T0 and T2. The results demonstrate that one week (T1) of local treatment leads to an improvement in sperm quality. However, this was not maintained one month (T2) after therapy, as seminal parameters at this time are similar to the pre-treatment values (T0), indicating the recurrence of the disease one month after therapy.
Keywords: Equine semen; Pyospermia; Seminal vesicle